Феохромоцитома: сучасні підходи до діагностики та лікування - Товкай, О. А. (Clinical Endocrinology and Endocrine Surgery, 2012)
The paper analyzed the literature data and own data concerning modern approaches to diagnostics and treatment of adrenal pheochromocytoma. The most reliable laboratory test is daily urinary metanephrines. The best option for surgical treatment is laparoscopic adrenalectomy which allows to remove even bilateral and very large (up to 16 cm) tumors with minimal injury. The technique and equipment of laparoscopic adrenalectomy on the right and left side are well described.